Change in electron and hole electrical conductions in OLEDs with different doping concentrations of 4CzIPN. Issue 1 (3rd July 2022) - Sato, Ryo; Ichino, Yusuke; Seike, Yoshiyuki; Mori, Tatsuo
Abstract: There are many reports on thermally activated delayed fluorescence (TADF) organic light-emitting diodes (OLEDs) with the external quantum efficiency achieving 30%. We investigate the electrical conduction of 4CzIPN-based TADF OLEDs depending on doping concentration of 0, 10, 20 or 35 mol%. As the doping concentration of 4CzIPN is increased, the electrons injected into the 4CzIPN sites are easily hopping between the 4CzIPN sites. The drive voltage decreases but the power efficiency is not remarkably improved. Since the red-shift of EL spectra at a constant current density is observed with doping concentration, the main carrier recombination zone is found to move with doping concentration.